Transactional Comparative Analysis of Ijarah and Al Ijarah Al Muntakiya Bit Tamlik in Islamic Banks - Asep Dadang Hidayat; Sofyan Al-Hakim; Iwan Setiawan (al-Afkar, Journal For Islamic Studies, 2023)
This research is to find out how ijarah and al-Ijarah al-Muntakiya bit Tamlik (IMBT) transactions are carried out in Islamic banks. The implementation of leasing transactions with ijarah schemes and IMBT in sharia bank products is in accordance with sharia principles. The implementation of ijarah transactions in Islamic banks refers to the provisions of the Fatwa of the National Sharia Council of the Indonesian Ulema Council (DSN-MUI) and Supreme Court Regulation Number 2 of 2008 concerning Compilation of Sharia Economic Law (KHES). There is a comparison with the implementation of the transfer of ownership of the leased object to IMBT, the transfer of the object for lease can only be attempted if the ijarah contract has ended, the option for transferring the object for lease can be attempted by promise (wa'ad). buy and sell. So there are no provisions in the IMBT contract based on the transfer of object ownership by promise (wa'ad). grants, this issue is contradictory because there is a reward that must be given by the customer (mustajir) to the bank for the object of the IMBT contract.